Meningkatkan Literasi Keuangan di Pedesaan Indonesia: Studi Kasus Pendidikan yang Didukung OJK di Jembayan Dalam - Henrika, Margareth (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study evaluates the effectiveness of a financial literacy program conducted with the Financial Services Authority (OJK) in Jembayan Dalam Village to enhance students' knowledge and financial decision-making skills. The focus is to understand the impact of financial literacy education on budgeting, saving, and money management in a rural context. Using a qualitative approach, data were collected through semi-structured interviews with students and teachers, classroom observations, and analysis of participation logs. The results show a significant improvement in students' financial literacy, particularly in budget planning and saving habits, through interactive learning. Teachers reported that students became more confident in managing finances, with the program being relevant to their daily lives. Student engagement was high, and they began applying financial concepts at home, indicating knowledge transfer to families. This study underscores the importance of financial literacy tailored to the needs of rural communities with limited access to financial resources. The findings contribute to the development of similar programs and suggest the need for further research to assess long-term impacts and the role of digital technology in program delivery.